2014
DOI: 10.1590/s0100-29452014000500001
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and acetogenins in Annonaceae development: biological considerations

Abstract: -Chemical studies of the plant family Annonaceae have intensified in the last several decades due to the discovery of annonaceous molecules with medicinal potential (e.g., benzylisoquinoline alkaloids and acetogenins). Approximately 500 alkaloids have been identified in 138 Annonaceae species in 43 genera. In addition, until 2004, 593 annonaceous acetogenins (ACGs) had been identified, from 51 species in 13 genera.This suggests that plants from this family allocate important resources to the biosynthesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
(22 reference statements)
0
28
1
3
Order By: Relevance
“…Although the role of acetogenins for the plant is not entirely known, their toxicity against arthropods or insects suggests that they constitute forms of chemical defense for all parts of the plant [4,27]. It was demonstrated that ACGs are biosynthesized during the organogenesis of the seeds, and it is suggested that ACGs can be used as antimicrobials or toxic compounds for animals, implying an early defense mechanism against phytopathogens or predators as a survival strategy in this species [28].…”
Section: Effect Of Ultrasound-assisted Extraction (Uae) On the Total mentioning
confidence: 99%
“…Although the role of acetogenins for the plant is not entirely known, their toxicity against arthropods or insects suggests that they constitute forms of chemical defense for all parts of the plant [4,27]. It was demonstrated that ACGs are biosynthesized during the organogenesis of the seeds, and it is suggested that ACGs can be used as antimicrobials or toxic compounds for animals, implying an early defense mechanism against phytopathogens or predators as a survival strategy in this species [28].…”
Section: Effect Of Ultrasound-assisted Extraction (Uae) On the Total mentioning
confidence: 99%
“…Phytochemical studies of this family have reported the presence of alkaloid (Malebo et al, 2013 ; Kouam et al, 2014 ; Soares et al, 2015 ), cyclopeptides (Wu P. et al, 2014 ; Moghadamtousi et al, 2015 ), flavonoids (Lage et al, 2014 ; Chokchaisiri et al, 2015 ), terpenoids (Annan et al, 2013 ; Rabelo et al, 2016 ), and lignans (Moreira et al, 2013 ; Nguyen et al, 2015 ; Rayanil et al, 2016 ). Several bioactivities including antimalarial (Frausin et al, 2014 ; Meira et al, 2015 ), antiplatelet, (Thang et al, 2013a ; González-Esquinca et al, 2014 ), and anti-inflammatory activity (Kandimalla et al, 2016 ) are just to name a few. Cytotoxicity of Annonaceous acetogenins has made this family of major interest for novel anti-cancer drugs (Han et al, 2015 ; Yang et al, 2015 ).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…However, A. macroprophyllata and A. purpurea had flowers at the end of the dry season and towards the beginning of the rainy season and began fruiting at the end of the rains. Their seeds likely remain dormant for at least six months or until the next rainy season starts (González-Esquinca et al 2014).…”
Section: Alma Rosa González-esquinca Et Almentioning
confidence: 99%